24.2k views
3 votes
Solve for this equation:
x(x+3)(x+3)=0

User Alnitak
by
4.5k points

2 Answers

6 votes

Answer:

x = 0 or x = -3 or x = -3

Explanation:

set up factors as:

x = 0

x + 3 = 0

x + 3 = 0

the first will remain as x = 0 while the others become x = -3 once subtracted

i hope this helped!

User Chris VCB
by
4.6k points
6 votes

Answer:

x^3+6x^2+9x

if you are trying to find the original function

if not, and you are trying to find the zeros is

x=-3

x=0

Explanation:

multiply x(x+3)

x^2+3x

then multiply that by x+3 and that should give you the answer

User Sasindu H
by
5.3k points